Transcultural diabetes nutrition algorithm : a Malaysian application - Hussein, Zanariah; Hamdy, Osama; Chia, Yook Chin; Lim, Lin Shueh; Natkunam, Santha Kumari; Hussain, Husni; Tan, Ming Yeong; Sulaiman, Ridzoni; Mohd Yusof, Barakatun Nisak; Siew, Winnie Swee Chee; Marchetti, Albert; Hegazi, Refaat A.; et al. (Hindawi Publishing Corporation, 2013)
Glycemic control among patients with prediabetes and type 2 diabetes mellitus (T2D) in Malaysia is suboptimal, especially after the continuous worsening over the past decade. Improved glycemic control may be achieved through a comprehensive management strategy that includes medical nutrition therapy (MNT). Evidence-based recommendations for diabetes-specific therapeutic diets are available internationally. However, Asian patients with T2D, including Malaysians, have unique disease characteristics and risk factors, as well as cultural and lifestyle dissimilarities, which may render international guidelines and recommendations less applicable and/or difficult to implement. With these thoughts in mind, a transcultural Diabetes Nutrition Algorithm (tDNA) was developed by an international task force of diabetes and nutrition experts through the restructuring of international guidelines for the nutritional management of prediabetes and T2D to account for cultural differences in lifestyle, diet, and genetic factors. The initial evidence-based global tDNA template was designed for simplicity, flexibility, and cultural modification. This paper reports the Malaysian adaptation of the tDNA, which takes into account the epidemiologic, physiologic, cultural, and lifestyle factors unique to Malaysia, as well as the local guidelines recommendations.